DRTA IN ENHANCING STUDENTS’ READING SKILL - Rizka Indahyanti; Sitti Nurjannah; Lindi La Uni (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2023)
The aim of this study is to determine the enhancement of students' reading comprehension through the implementation of Directed Reading-Thinking Activity (DRTA). The research design employed a Quasi-experimental approach, involving the participation of two distinct groups. The study consisted of an experimental group and a control group, with multiple choice tests being used as the research instrument. This research is carried out at SMA Negeri 8 Maros by selecting the first-year students as the target population. The researcher utilized the cluster random sampling technique, selecting class X IA 1 as the experimental group and X IS 1 as the control group. Data is collected through both pretest and posttest assessments. The pretest is administered to assess the students' prior reading achievement prior to implementing the treatment, while the posttest is conducted to determine the students' achievement following the treatment. The research examines the usage of DR-TA as the independent variable in teaching reading comprehension, while the dependent variable is the students' achievement in acquiring reading comprehension. The data analysis of the students' pretest and posttest revealed that the mean value of the experimental group (71.10) is higher than that of the control group (48.90). It suggests that implementing the DR-TA method enhances students' reading performance.